The 370 Da inhibitor of the sodium pump in the plasma of haemodialysis patients - David Makanjuola; Gwyn A. Lord; Philip J. Hilton (Karger Publishers, 2021)
Background: Previous studies have shown that a molecule of mass 370 Da that inhibits the sodium pump can be extracted from human placentas and from the concentrated plasma or ultrafiltrate of volume-expanded patients. Aim: To study the abundance of the 370 Da molecule and its changes across dialysis in a population of patients with renal failure treated by haemodialysis. Methods: 4 mL pre- and post-dialysis blood samples (2 mL plasma) were taken from patients receiving intermittent haemodialysis and analysed by high performance liquid chromatography (HPLC) coupled to high sensitivity mass spectrometry. Results: In over half the study population, the 370 Da molecule was present in an abundance that exceeded the limit of quantitation. Most patients experienced a marked fall in the abundance of the molecule over a haemodiafiltration (HDF) session, though exceptions were seen in two individuals both of whom showed clear evidence for the presence of two structural isomers of the 370 Da molecule. Conclusions: Advanced renal failure is frequently accompanied by an increased abundance of a 370 Da inhibitor of the sodium pump and that abundance is strongly impacted by haemodialysis. The technique described here could readily be applied to other clinical situations where sodium pump inhibition might be anticipated, such as hypertension, pregnancy and fetal medicine and thereby lead to a better understanding of the physiology and patho-physiology of these conditions.